Vitamin D insufficiency is high in Malaysia: A systematic review and meta-analysis of studies on vitamin D status in Malaysia - Mohd Saffian, Shamin; Jamil, Nor Aini; Mohd Tahir, Nor Asyikin; Hatah, Ernieda (Frontiers in Nutrition, 2022)
Purpose: To estimate the vitamin D status of participants residing in Malaysia. Methods: PubMed, Scopus, Web of Science, and MyJurnal were searched up to June 2022 without language restrictions. Studies that reported the 25-hydroxyvitamin D (25(OH)D) concentrations and defined their cut-off for deficiency or insufficiency from healthy participants residing in Malaysia were included. The random effects model was used to pool vitamin D status using established cut-offs of <30nmol/L, <50nmol/L, and <75nmol/L according to age group. Results: From 299 studies screened, 32 studies were included in the meta-analysis. The pooled proportion for <30nmol/L was 21% (95% CI 9–36, n=2,438 from 10 studies), while the pooled proportion <50nmol/L was 64% (95% CI 56–72, n=13,977 from 30 studies), and <75nmol/L was 85% (95% CI 61–100, n=1,376 from 5 studies). Heterogeneity was high (I² ranged from 98% to 99%). Higher proportions of vitamin D insufficiency (defined as <50nmol/L) were found in participants living in the urban areas (compared to rural areas), in females (compared to males), and in Malays and Malaysian Indians (compared to Malaysian Chinese) ethnicities. Conclusion: More than half of Malaysians have insufficient vitamin D levels, despite being a country that is close to the equator. We strongly urge prompt public health measures to improve the vitamin D status in Malaysia. Systematic review registration PROSPERO: CRD42021260259